2020
DOI: 10.1097/hco.0000000000000816
|View full text |Cite
|
Sign up to set email alerts
|

The placenta as the window to congenital heart disease

Abstract: Purpose of review There is an increasing recognition that structural abnormalities and functional changes in the placenta can have deleterious effects on the development of the fetal heart. This article reviews the role of the placenta and the potential impact of placental insufficiency on fetuses with congenital heart disease. Recent findings The fetal heart and the placenta are directly linked because they develop concurrently with shared regulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The underlying pathophysiologic connection between this maternal‐placental‐fetal axis of interaction may be related to shared molecular signaling and regulatory pathways. 50 For example, Llurba et al found that biomarkers of chronic hypoxia, antioxidant activity, and angiogenic factor expression of VEGF (vascular endothelial growth factor) were significantly increased in heart tissue from fetuses with CHD compared with controls. 5 Furthermore, PGF (placental growth factor) in maternal plasma was significantly decreased in pregnancies with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiologic connection between this maternal‐placental‐fetal axis of interaction may be related to shared molecular signaling and regulatory pathways. 50 For example, Llurba et al found that biomarkers of chronic hypoxia, antioxidant activity, and angiogenic factor expression of VEGF (vascular endothelial growth factor) were significantly increased in heart tissue from fetuses with CHD compared with controls. 5 Furthermore, PGF (placental growth factor) in maternal plasma was significantly decreased in pregnancies with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…While neovascularization is required for successful fetal development, aberrant regulation of the signaling pathways overseeing this process may lead to improper vessel network development in the form hypervascularization or vasculature malformation [38, 39] . Additionally, these structural abnormalities are associated with placental insufficiencies, which could result in lifelong adverse cardiometabolic health outcomes in both mothers and offspring [12, 13, 40] . While the data presented here are incapable of concluding the direct impact of placental miRNA dysregulation there is a growing body of literature, as well as the associations outlined here, that suggest dysregulation of placental miRNAs may be contributing to the developmental programming and propagation of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, such placental insufficiencies are associated with adverse gestational outcomes, such as fetal growth restriction, which itself serves as a significant risk indicator for the development of cardiovascular disease (CVD) later in life [9][10][11] . Considering placental development occurs concurrently with fetal heart development, and each organ utilizes common humoral growth signals, such as transforming growth factor-beta (TGFβ) and vascular endothelial growth factor (VEGF), deficiencies in the organogenesis of either organ may alter the formation of the other, initiating physiological changes with potential lifelong cardiovascular consequences [12][13][14] . While the associations between maternal cardiometabolic risk factors, placental insufficiency and offspring lifelong health outcomes are well defined [7,8,15] , the molecular mechanisms by which this developmental programming is established have yet to be robustly delineated.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the placenta in the development of CHD and its outcome has become an area of increasing interest. 9 , 10 Savla et al 2 included preeclampsia, a complication of impaired placentation, as an environmental variable in their risk model. The rationale for this is several‐fold as there are a number of ways in which preeclampsia might be implicated in the causal pathway to adverse outcome in infants with critical CHD.…”
mentioning
confidence: 99%
“…The rationale for this is several‐fold as there are a number of ways in which preeclampsia might be implicated in the causal pathway to adverse outcome in infants with critical CHD. First, disorders of placentation in general, and preeclampsia in particular, are strongly associated with fetal CHD, 10 , 11 with an increased risk of CHD associated with earlier‐onset preeclampsia, suggesting a dose‐timing or dose‐duration effect. 12 Remodeling of the spiral arteries is a critical element in normal placentation (and impaired in preeclampsia), events that occur in the first trimester concurrent with early development of the heart.…”
mentioning
confidence: 99%